BEFORE SCHOOL EDUCATION MODERN IN THE APPROACH THE WORLD EXPERIENCES - Isayeva Deal Sodikovna; Kurbonova Umida Sharifovna (Journal of new century innovations, 2023)
This is it in the article in our country developed going before school education in the system news , take going huge reforms , new set up happening before school education organizations , family non-state and private of kindergartens development , before school education in the system modern of approach the world experiences about word goes _ Organization done activity in the process one how many kind of education forms is described and this study forms to the children to be given of knowledge efficiency to increase help gives _